2006
DOI: 10.1074/jbc.m512185200
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutations of T4 Helicase Loading Protein (gp59) Reveal Multiple Modes of DNA Polymerase Inhibition and the Mechanism of Unlocking by gp41 Helicase

Abstract: The T4 helicase loading protein (gp59) interacts with a multitude of DNA replication proteins. In an effort to determine the functional consequences of these protein-protein interactions, point mutations were introduced into the gp59 protein. Mutations were chosen based on the available crystal structure and focused on hydrophobic residues with a high degree of solvent accessibility. Characterization of the mutant proteins revealed a single mutation, Y122A, which is defective in polymerase binding and has weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
2
14
1
Order By: Relevance
“…The helicase is loaded onto the lagging strand template by the helicase loader protein (gp59) (9,10). gp59 plays an additional role as a "gatekeeper" of the replisome by coordinating the assembly of the primosome with the initiation of leading strand DNA synthesis through a direct interaction with the leading strand polymerase (11)(12)(13). Finally, gp32 plays a central role in most aspects of DNA metabolism, including DNA replication (14).…”
mentioning
confidence: 99%
“…The helicase is loaded onto the lagging strand template by the helicase loader protein (gp59) (9,10). gp59 plays an additional role as a "gatekeeper" of the replisome by coordinating the assembly of the primosome with the initiation of leading strand DNA synthesis through a direct interaction with the leading strand polymerase (11)(12)(13). Finally, gp32 plays a central role in most aspects of DNA metabolism, including DNA replication (14).…”
mentioning
confidence: 99%
“…3 Isothermal titration calorimetry experiments were consistent with a stoichiometry of 0.75 gp59 subunit to 1 gp41 subunit with a dissociation constant of ϳ150 nM. 3 The electron microscopic studies on the structure of the gp41-gp61 complex revealed two hexamers in a 1:1 stoichiometry (19). Based on the collective data, it could be postulated that gp59 should form a functional higher order complex ranging from tetramer to hexamer.…”
mentioning
confidence: 86%
“…Cross-linking experiments observed complexes of gp59 up to a pentamer in the presence of gp32, gp41, and DNA. 3 Isothermal titration calorimetry experiments were consistent with a stoichiometry of 0.75 gp59 subunit to 1 gp41 subunit with a dissociation constant of ϳ150 nM. 3 The electron microscopic studies on the structure of the gp41-gp61 complex revealed two hexamers in a 1:1 stoichiometry (19).…”
mentioning
confidence: 92%
See 2 more Smart Citations